Contextualizing Human Resource Management Practices: The Philippine Experience for an HEI - Cabahug, Monriud; Ferrater-Gimena, Judy Ann (JPAIR Multidisciplinary Research, 2018)
Human resource management is extremely imperative for any association, particularly in the scholarly setting. The employees should be given a clear direction on where they are going to when they become part of the organization. This study aimed to assess the extent of the manifestation of a sound human resource management (HRM) practices of the University of Cebu-Banilad as assessed by the teaching and the non-teaching staff.  The results of this investigation will be used as basis for the formulation of interventions in the current human resource management system.  This study utilized the predictive relational method of research using a researcher-made questionnaire. Using purposive sampling, there were forty-seven (47) employees who participated in this investigation.  Percent, median, mode, and range were computed to analyze the data.  The results revealed that wage and salary, administration, training and development, and change in personnel status were practiced in some cases only.   Further, career management, job security and status, working condition, and people empowerment were the factors that motivate them in some cases to perform well in their respective job functions.  There is a significant relationship between the age and the respondents' perception of the human resource management practices.  However, there was no connection between the sexual orientation of the representatives and their reactions to the motivational variables.
Keywords: Human resource management; motivation; correlation; Cebu City; Philippines